Knowledge and practice of menstrual hygiene among adolescent school girls in Umunna, Imo State, Southeast Nigeria: implications for parents, healthcare providers and policy makers - Duru, Chika O.; Ikeanyi, Eugene M.; Merenu, Irene (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Menstrual hygiene management is critical in the life of the woman. For optimal attendance and participation in school activities, future reproductive and sexual health; quality menstrual hygiene practice is crucial. The objective of this study was designed to assess the knowledge, practice and challenges of menstrual hygiene management among the adolescents Methods: A cross-sectional study was conducted on a community secondary school girls from 1st May to 30th June 2016. Data was collected with a semi-structured pre-tested questionnaire and analyzed with statistical software as appropriate. Results: A total of 416 (97.4%) of the respondents were analyzed. Their mean chronological age and age at menarche were 15±2.1 years and 12.9±0.7 years respectively. Most (77.9%) of the respondents had premenarchal menstrual hygiene knowledge and mothers (68.8%) were the main source of information. Sanitary pad (56.3%) and cloth (31.2%) were the most commonly used absorbents. Sanitary pad use was higher in respondents whose mothers had higher level education (RR=6.3, p<0.001). Most of the respondents changed absorbent twice or less daily (77.4%), bathed at least twice (77.4%), washed vulvoperineal region with soap and water (50.2%) and wiped perineum front to back (72.8%). Burning (51.9%) and refuse dump (26.0%) were the main disposal methods and 48.1% washed hands before and after changing menstrual absorbent materials. Main menstrual disturbances were abdominal pain (37.7%) and malaise (18.5%) and main intervention was medication from patent medicine store (47.2%). Menstruation-related school absenteeism was 30.8%. Conclusions: There was poor premenarchal menstrual awareness and inappropriate menstrual hygiene practices among adolescent schoolgirls.